The role of large language models in dental diagnosis, treatment planning, and prognosis - Issa, Julien; Sohrabniya, Fatemeh; Brinz, Janet; Dyszkiewicz-Konwińska, Marta; Chaurasia, Akhilanand (Journal of Stomatology, 2025)
Large language models (LLMs) represent sophisticated deep learning algorithms that excel in various natural language processing tasks. These advanced models find applications across multiple industries, such as healthcare, finance, and entertainment. They are utilized for a range of functions, from language translation to powering chatbots and artificial intelligence (AI) assistants. This literature review aimed to evaluate the impact of LLMs on the field of dentistry, highlighting both the challenges and opportunities they present in enhancing patient care. Specifically, it focused on improvements in diagnostics, treatment planning, and prognostic accuracy facilitated by LLMs. The review explored the latest advancements in LLM technology, examining their architectural frameworks and applications across different dental specialties. LLMs show significant potential in advancing patient education, dental diagnosis, treatment planning, and prognostic assessments. However, to fully harness the capabilities of these models within dentistry, continuous research and development efforts are necessary to address their limitations and ethical concerns. The review underscored the importance of ongoing innovation and adaptation to maximize the benefits of LLMs in dental practice, ensuring they contribute to improved patient outcomes and more efficient clinical workflows. Integrating LLMs into dental care could enhance diagnostic accuracy and enable personalized treatment plans, promising a new era in dental healthcare.